Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-11-09T17:27:08+01:00
A)(1½-3*1⅓):2½=(1 1/2-4):2 1/2=(-2 1/2):2=(-10)
b) 3¾*1⅕+(-1½):2⅖-¼=4 1/2+(-5/8)-1/4=3 7/8- 1/4=3 5/8
c)(3 8/15+1 3/5):(4 1/7 -10 3/28)=5 2/15:(-6 1/28)=2156/2535
2009-11-09T17:31:29+01:00
A). = (1,5 - 3/1 * 4/3) : 5/2 = (1,5 - 4) * 5/2 = - 5/2 * 2/5 = -1
b). niestety nie widzę. :)
2009-11-09T17:35:12+01:00
A)(1½-3*1⅓):2½=(1½-4):2½=1
b) 3¾*1⅕+(-1½):2⅖-¼=4,5+(-5/8)-¼=3i5/8

c)(3 8/15+1 3/5):(4 1/7 -10 3/28)=(3 8/15 +1 9/15):(4 4/28-10 3/28)=
4 17/15: (-6 1/28)=2156/2535